Recasting Ovid: an interrogation of the rhetoric of status dynamics and its analytical purchase in performance pedagogy and textual analysis - Roberts, Sarah Elizabeth (My University, 2014)
This thesis seeks to define and interrogate the rhetoric of status in representations of inter-active encounters in order to probe its efficacy as a pedagogical tool within performance training and text analysis. Within the paradigm of an improvisation pedagogy, which appears to disrupt an approach to drama as a form of literature focusing on social dynamics expressed through inter-personal and reciprocal obligations, Keith Johnstone suggests the value of playing status-based encounters. My study undertakes a theoretical approach to examining and defining the rhetoric that accrues to encounters that are undergirded by inequitabilities, amplifying and extending Johnstone’s central propositions. To the extent that status positions are as embedded in social behaviour and values, cultural habits and routines, the thorough theoretical articulation and interrogation of the representation of power dynamics, specifically in relation to the notion of a self at the centre of multiple subject positions, profits from an inter-disciplinary scholarly practice. A conceptual framework informed by key ideas from anthropological and social philosophy (specifically that of Georg Simmel) and cultural studies allows for identifying ways in which “symbolic forms” operate within the circuit of producing meanings and values. The extent to which Simmel’s seminal formulations regarding group formation and affiliation, power exercised at the level of inter-personal encounter, expressions of social difference and relations between subjectivity and culture, augment Johnstone’s lexicon will be advanced through a range of textual close readings to test the value of inter-disciplinary practice. The response-based vocabulary of status rhetoric is deployed as a tool for textual close-reading. Ovid’s great mythic poem provides a template for interweaving a range of case studies that exemplify ways in which the tropes and metaphors of position are inflected through performance languages and the extent to which spontaneous encounters are rendered and re-presented. Interrogating asymmetries from within a context in which inequitable relations are inherently and overtly pronounced problematizes the subject under interrogation in terms of cultural perspective and linguistic facility. The merits of an inter-active, outwardly-focused, response-based model of generating performances are advanced as a paradigm serving both the needs and rights of an individual while promoting the collaboration and collective interplay crucial to ensemble-based performances. Improvisation pedagogy implicitly proposes testing the tensions between determination and freedom situated in a historically conditioned moment. While the core focus is the articulation of status dynamics in encounters between social subjects, the interplay between persons and “things” and a lone individual within a spatio-temporal situation are equally productive sites in which status dynamics are articulated and observed. In contemporary South Africa the multi-faceted dimensions of what it means to live, work and negotiate cultural pluralities and radical disparities in agency (along with fundamental divergences regarding both subjectivity and the sense of communitas) increasingly compel the need for hybridity in teaching, learning and the capacity to produce socially meaningful ‘art’. The challenge in performance training today may well be to re-conceptualize acting as a collective ensemble project inseparable from intellectual inter-disciplinary scholarship. In this model, the working consensus of the collective becomes the goal, medium and the message as the ensemble assumes “authorship” of the performance and theatre is restored to a political and democratic praxis.